The Relationship Between Online Games And Behavioral Changes In Pregnant Women At Surabaya In 2021 - azyvati karesna putera; Salmon Charles P. T. Siahaan (Lambung Mangkurat University, 2022)
Online games are types of games that can be accessed by many people using a device connected to the internet. The various types of available games can easily attract the interest of all ages and people with certain health conditions such as pregnant women. Online games whose initial purpose for entertainment can have a negative impact both physically and mentally on users. Behavioral changes in pregnant women that are not appropriate can have a negative impact on the condition of the pregnant women and fetus. The purpose of the study was to explain the relationship between online games and behavioral changes in pregnant women. This research used an observational analysis type and prospective cohort design, the sampling random using a questionnaire conducted to pregnant women in the first & second trimesters at Puskesmas Made Surabaya from August to December 2021 which will be tested with the chi-square. There is a significant relationship between several variables. There is a positive relationship between playing duration and pathologic conditions with p=0.014 and depression with p = 0.036. There is a positive relationship between game types and pathologic conditions with p = 0.033 and knowledge improvement with p = 0.047. There is a relationship between online games and behavioral changes in pregnant women, both from the duration of playing or the type of game chosen.